What is pre‐reflective self‐consciousness an awareness of? An argument for the egological view. - Barbieri, Alberto (Southern Journal of Philosophy, 2025)
The nature of pre‐reflective self‐consciousness—namely, the putative non‐inferential self‐consciousness involved in unreflective experiences—has become the topic of considerable debate in recent analytic philosophy of consciousness, as it is commonly taken to be what makes conscious mental states first‐personally given to their subject. A major issue of controversy in this debate concerns what pre‐reflective self‐consciousness is an awareness of. Some scholars have suggested that pre‐reflective self‐consciousness involves an awareness of the experiencing subject. This "egological view" is opposed to the "non‐egological view," according to which the subject is just aware of their own occurrent mental state in being pre‐reflectively self‐conscious. In this article, I argue in favor of the egological view. The argument I develop is a qualified version of a line of reasoning originally provided by Rosenthal and builds on a proper clarification of the ontological status of token mental states. More precisely, I argue that token mental states are structured "fact‐like" entities having their subject among their constituents. Accordingly, one cannot be aware of one's own occurrent mental state without thereby being aware of oneself. I conclude by dismissing a potential objection to my argument.